2008
DOI: 10.1136/bjsm.2008.051425
|View full text |Cite
|
Sign up to set email alerts
|

The common mechanisms of anterior cruciate ligament injuries in judo: a retrospective analysis

Abstract: Grip style may be associated with ACL injury occurrence in judo. In addition, direct contact due to the opponent's attack may be a common mechanism for ACL injuries in judo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Ardern et al found similar results for athletes from different kinds of ball sports, 61% of whom had attempted to return to their preinjury level 35. For judo athletes, it has been suggested that ACL rupture is the most serious knee injury 23. Until now, this suggestion has not been confirmed by the literature 2 19–22 36 37.…”
Section: Discussionmentioning
confidence: 90%
“…Ardern et al found similar results for athletes from different kinds of ball sports, 61% of whom had attempted to return to their preinjury level 35. For judo athletes, it has been suggested that ACL rupture is the most serious knee injury 23. Until now, this suggestion has not been confirmed by the literature 2 19–22 36 37.…”
Section: Discussionmentioning
confidence: 90%
“…However, results on the frequency of knee injuries while performing this technique are discordant 38. Moreover, there is a high risk of repeated injuries after the first lesion sustained during these shoulder throws, mostly caused by the too quick resumption of physical activity after the sustained trauma 26.…”
Section: Resultsmentioning
confidence: 99%
“…Knee sprains, which mainly affect the MCL and ACL in the judo population,47 are often caused by leg techniques, for example, O Soto Gari 38 48. Also, having a different grip style from the opponent seems to be a risk factor for ACL injuries 38. Lesions of the collateral ligament vary according to the violence of the trauma 38.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study of Japanese judo players found that certain stances left players exposed to kicks that could result in contact ACL ruptures [16]. This study suggests that education about risky stances and movements can be useful in reducing contact ACL injuries among judo players [15].…”
Section: Crimson Publishersmentioning
confidence: 98%